2020
DOI: 10.3390/f11111190
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Selection for Forest Tree Improvement: Methods, Achievements and Perspectives

Abstract: The breeding of forest trees is only a few decades old, and is a much more complicated, longer, and expensive endeavor than the breeding of agricultural crops. One breeding cycle for forest trees can take 20–30 years. Recent advances in genomics and molecular biology have revolutionized traditional plant breeding based on visual phenotype assessment: the development of different types of molecular markers has made genotype selection possible. Marker-assisted breeding can significantly accelerate the breeding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 162 publications
0
75
0
Order By: Relevance
“…Breeding forest tree species for abiotic stress tolerance by conventional techniques is complicated, not only because of their long generation time and large size, but also because these traits are regulated by loci that are widespread across the whole genome with both additive and interaction effects [3]. Recently, the stimulation of induced defense/adaptation responses by "priming" has emerged as a promising strategy to increase resilience to adverse conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Breeding forest tree species for abiotic stress tolerance by conventional techniques is complicated, not only because of their long generation time and large size, but also because these traits are regulated by loci that are widespread across the whole genome with both additive and interaction effects [3]. Recently, the stimulation of induced defense/adaptation responses by "priming" has emerged as a promising strategy to increase resilience to adverse conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that non-parametric models perform better than parametric models because they capture both additive and non-additive effects (e.g., dominance, epistasis). They can predict phenotypes better than the parametric models, especially where non-additive effects are important (Lebedev et al 2020). For instance, in eucalyptus, RKHS had slightly better predictive abilities than four other models for traits with lower heritabilities (i.e.…”
Section: Effect Of Heritability and Training Population Size On Genommentioning
confidence: 99%
“…Multivariate methods that analyze multiple SNP alleles (sometimes grouped by functional categories such as the genes in which those SNPs occur) and multiple phenotypes in parallel have shown improved power to detect associations of genotypes with environmental variables (Rellstab et al, 2015;Forester et al, 2018) and with phenotypic variation (Kaakinen et al, 2017;Luo et al, 2020). Genomic selection is another approach to parallel analysis of many SNP loci with phenotypic information, and considerable interest has been shown in applying this method to forest tree breeding (reviewed by Lebedev et al, 2020).…”
Section: Future Directionsmentioning
confidence: 99%